ISSUES OF INCREASING INVESTMENT ACTIVITY IN THE TEXTILE INDUSTRY OF UZBEKISTAN (International Congress on Economics, Management and Business Studies, 2026)
This article analyzes the issues of increasing investment activity in the textile industry of Uzbekistan and substantiates the tasks of attracting greater volumes of foreign direct investment to the national market.
Keywords: oil, gas, gold mining, metallurgy, and other industries